No Effects of D-Cycloserine Enhancement in Exposure With Response Prevention Therapy in Panic Disorder With Agoraphobia: A Double-Blind, Randomized Controlled Trial. Issue 5 (October 2017) - Hofmeijer-Sevink, Mieke Klein; Duits, Puck; Rijkeboer, Marleen M.; Hoogendoorn, Adriaan W.; van Megen, Harold J.; Vulink, Nienke C.; Denys, Damiaan A.; van den Hout, Marcel A.; van Balkom, Anton J.; Cath, Danielle C.
Abstract: Purpose/Background: D-cycloserine (DCS) is a partial N-methyl-D-aspartate receptor agonist that potentially augments response to exposure therapy in anxiety disorders by enhancing extinction learning. This randomized, double-blinded, placebo-controlled augmentation trial examined (1) the effectiveness of adding 125 mg of DCS to exposure therapy (before or directly after the first 6 treatment sessions) in patients with panic disorder with agoraphobia and (2) the effectiveness of DCS augmentation preceding exposure relative to DCS augmentation directly postexposure. Methods/Procedures: Fifty-seven patients were allocated to 1 of 3 medication conditions (placebo and pre-exposure and postexposure DCS) as an addition to 6 exposure sessions within a 12-session exposure and response prevention protocol. The primary outcome measure was the mean score on the "alone" subscale of the Mobility Inventory (MI). Findings/Results: No differences were found in treatment outcome between DCS and placebo, administered either pre-exposure or postexposure therapy, although at 3-month follow-up, the DCS postexposure group compared with DCS pre-exposure, exhibited greater symptom reduction on the MI-alone subscale. Ancillary analyses in specific subgroups (responders vs nonresponders, early vs late responders, severely vs mildly affected patients) did not reveal any between-group DCS versus placebo differences. Finally, the study did not find an effect of DCS relative to placebo to be specific for successful exposure sessions. Implications/Conclusions: This study does not find an effect of augmentation with DCS in patients with severe panic disorder and agoraphobia administered either pretreatment or directly posttreatment sessions. Moreover, no preferential effects are revealed in specific subgroups nor in successful exposure sessions. Yet, a small effect of DCS administration postexposure therapy cannot be ruled out, given the relatively small sample size of this study. Abstract : Supplemental digital content is available in the text.